2017
DOI: 10.1002/ijgo.12378
|View full text |Cite
|
Sign up to set email alerts
|

Defining quality of care during childbirth from the perspectives of Nigerian and Ugandan women: A qualitative study

Abstract: Objective: To explore what "quality of care" means to childbearing women in Nigeria and Uganda, as a means of ensuring that women's voices and opinions are prioritized when developing interventions to improve quality in maternity care provision. Methods:Qualitative methods, with a purposive sample of women in Nigeria and Uganda. Participants were asked to define quality of care and to provide examples of when it was and was not provided. Thematic analysis was used to synthesize findings based on an a priori fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 37 publications
(83 reference statements)
8
85
0
1
Order By: Relevance
“…The detailed findings of the review of internationally recognized intrapartum care practices were published as part of the 2016 Lancet Maternal Health Series . Quality of facility‐based childbirth care based on the views, needs, expectations, values, and preferences of women and healthcare providers, as well as service models that incorporated the agreed standards are published separately in this Supplement …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed findings of the review of internationally recognized intrapartum care practices were published as part of the 2016 Lancet Maternal Health Series . Quality of facility‐based childbirth care based on the views, needs, expectations, values, and preferences of women and healthcare providers, as well as service models that incorporated the agreed standards are published separately in this Supplement …”
Section: Resultsmentioning
confidence: 99%
“…A primary qualitative study was conducted in eight study facilities and facility catchment areas in Nigeria and Uganda. Detailed accounts of the study methods, procedures and results have been published separately . Briefly, in‐depth interviews (IDIs) and focus group discussions (FGDs) were conducted with women of reproductive age who had given birth in a health facility in the previous 12 months, as well as doctors, nurses/midwives, and healthcare administrators working in the study facilities.…”
Section: Methodsmentioning
confidence: 99%
“…While women themselves are the “gold standard” for information on their own needs and preferences, healthcare providers and administrators can provide interesting input to explore convergent and divergent perspectives on women's needs. This paper is part of a series on the BOLD project formative research; other aspects of the project are described in detail elsewhere in this Supplement …”
Section: Introductionmentioning
confidence: 99%
“…While the data are situated in the local health systems, the contextual enablers and barriers are common to many low‐resource maternity care facilities. The richness of data from multiple perspectives provided a comprehensive view on labor monitoring from the key stakeholders, and supplements the findings from other papers in this Supplement . This study may have been limited by the self‐reported practices from the health professionals, which can lead to social desirability bias, resulting in a narrative of “ideal situation” rather than the “actual situation” of labor monitoring.…”
Section: Discussionmentioning
confidence: 81%